Multivariate statistical analysis of the essential oils of five beilschmiedia species from Peninsular Malaysia (SCOPUS) - Wan Mohd Nuzul Hakimi Wan Salleh (Tanjung Malim, 2021)
Multivariate statistical analysis of the essential oils of five beilschmiedia species from Peninsular Malaysia (SCOPUS) by Wan Mohd Nuzul Hakimi Wan Salleh